Correlation of Knowledge and Foot Care with Reccurent Occurrence of Diabetic Foot Ulcer in Patients with Type 2 DM at Ulin Banjarmasin Hospital - Amaliah, Meina; Onieqie Ayu Dhea Manto; Dwi Sogi Sri Redjeki (Universitas Muhammadiyah Kalimantan Timur, 2025)
Diabetic foot ulcers (DFU) are a complication in patients with DM characterized by clearly visible wounds, usually on the soles of the feet, which can cause loss of sensation or nerve death. Factors affecting the incidence of UKD include lack of knowledge and implementation of foot care in patients with type 2 DM. Objective: Knowing the relationship between knowledge and foot care on the incidence of recurrent diabetic foot ulcers in patients with type 2 diabetes in RSUD Ulin Banjarmasin. Methods: Quantitative research method with a cross sectional approach. In this study, the sampling technique used was purposive sampling with a total of 51 respondents. Results: The results of the Spearman Rank test analysis showed a significant relationship between knowledge and foot care on the recurrence of diabetic foot ulcers. Knowledge has a moderate correlation (r = 0.371) and foot care has a strong correlation (r = 0.713).Conclusion: Based on the results of the study, the knowledge of respondents on the recurrence of UKD showed that 13.7% had good knowledge, 66.7% had sufficient knowledge and 2% had poor knowledge with the first ulcer. The implementation of foot care also showed that 17.6% had good implementation, 82.4% had sufficient implementation of foot care.